Queering the System from within: Autostraddle as a Method for Future Digital Worlds. - Obbard, Kiera; McLean, Lauren (Australian Feminist Studies, 2024)
Despite the harmful potentials of social media, the digital world appears to offer endless potential for change. A queer and feminist example is Autostraddle, a digital community and publication for LGBTQIA2s + people run by feminist queer and trans folx, that attempts to mitigate the potential harms of social media platforms while existing within and beyond its borders. Situating Autostraddle within the larger context of social media platforms and feminist communities online, this article considers how Autostraddle's original model queers the system from within (Tsika, Noah. 2016a. "CompuQueer: Protocological Constraints, Algorithmic Streamlining, and the Search for Queer Methods Online." Women's Studies Quarterly 44 (3/4): 111–130), creatively reworks corporate platforms (Trott, Verity Anne. 2023. Feminist Activism and Platform Politics. E-Book: Abingdon: Routledge), and designs social media for difference (McPherson, Tara. 2014. "Designing for Difference." Differences 25 (1): 177–188). Autostraddle makes use of the following queer methods to reconstruct the digital landscape for queer humans: Queer reversal and the two T's (transparency and transformation). Through employing practices such as placing an emphasis on community and a culture of care, enacting transparency to make the invisible visible, and implementing data policies and safety practices that prioritise users over profits, Autostraddle contributes to critical reimaginings for the future. Examining Autostraddle's methods demonstrates one approach for incorporating feminist and queer theory to (re)envision a more equitable digital future.